9th International Vacuum Microelectronics Conference
DOI: 10.1109/ivmc.1996.601808
|View full text |Cite
|
Sign up to set email alerts
|

Work function estimate for electrons emitted from nanotube carbon cluster films

Abstract: Relying on the obtained theoretical and expenmental results the electron work function from the nanotube carbon film was &mated. It was shown that these structures have a low work function, substantially lower than for graphite. Under estimation we regarded the influence of the film surface relief on its emission ability.Even first investigation results for electron field emission from the thin films containing nanotube carbon structures we developed [l] have shown that these films are promising for emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 3 publications
(2 reference statements)
0
18
0
Order By: Relevance
“…This trend is observed on all tested samples. Field emission from refractory metals with work functions Ͼ3.5 eV is practically temperature independent below 1000 K. The observed strong thermal dependence at low temperatures indicates a different mechanism, such as work function less than 1.3 eV, as reported by Gulyaev et al 8 The temperature dependence of field emission has a different functionality with the work function ͑͒ and field enhancement factor ͑␤͒ than is produced from FowlerNordhiem fits. 23 Thus, it is theoretically possible to determine the and ␤ independently with I -V and I -T data provided a metallic electron tunneling model is followed.…”
Section: Low Work Function Mechanismsmentioning
confidence: 50%
See 1 more Smart Citation
“…This trend is observed on all tested samples. Field emission from refractory metals with work functions Ͼ3.5 eV is practically temperature independent below 1000 K. The observed strong thermal dependence at low temperatures indicates a different mechanism, such as work function less than 1.3 eV, as reported by Gulyaev et al 8 The temperature dependence of field emission has a different functionality with the work function ͑͒ and field enhancement factor ͑␤͒ than is produced from FowlerNordhiem fits. 23 Thus, it is theoretically possible to determine the and ␤ independently with I -V and I -T data provided a metallic electron tunneling model is followed.…”
Section: Low Work Function Mechanismsmentioning
confidence: 50%
“…1, 6 On the other hand, Collins and Zettl 2,7 and Bonard et al 4 observe changes in the slope of the current-voltage behavior in several nanotube samples which they claim suggest a more complicated model than Fowler-Nordheim tunneling. Furthermore, both Gulyaev et al 8 and Rinzler et al 9 have reported unusual temperature-driven changes in field emission current from carbon nanotubes. Gulyaev et al conclude that the strong thermal dependence indicates that both SWNTs and MWNTs are low work function emitters.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3] Carbon nanotube ͑CNT͒ material can be produced in macroscopic quantities by using graphite evaporation in the course of arc discharge or laser ablation or by using thermal decomposition of hydrocarbons. [1][2][3] Carbon nanotube ͑CNT͒ material can be produced in macroscopic quantities by using graphite evaporation in the course of arc discharge or laser ablation or by using thermal decomposition of hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Carbon nanotube ͑CNT͒ material can be produced in macroscopic quantities by using graphite evaporation in the course of arc discharge or laser ablation or by using thermal decomposition of hydrocarbons. 1,[6][7][8][9] From the viewpoint of the field emission ͑FE͒ applications, there is another imperfection of oriented CNT material -a very dense packing of nanotubes. This restrict both the investigations of nanotube's properties and their applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In the present article we assess the electronic work function from this material by analyzing experimental results obtained for field and thermal emission from the surface of thin nanotube carbon cluster ͑tubelene͒ films 4,5 and theoretical calculations. [1][2][3] In the present article we assess the electronic work function from this material by analyzing experimental results obtained for field and thermal emission from the surface of thin nanotube carbon cluster ͑tubelene͒ films 4,5 and theoretical calculations.…”
mentioning
confidence: 99%